The Influence of Unique Information in Briefs on Supreme Court Opinion Content. (3rd April 2019) - Hazelton, Morgan L. W.; Hinkle, Rachael K.; Spriggs, James F.
Abstract: Using a unique and vast dataset and new measures derived from natural language processing, we investigate the flow of information to the Supreme Court via briefs. Our study provides an opportunity to consider the often-nuanced role of information in policymaking. Building on prior work, we contribute in a number of important ways to our understanding of the influence of information on policy generally and briefs on the Court's decisions specifically. We consider how the repetition of information can signal policy coalescence across interested groups and individuals, as well as proxy quality and exert a psychological effect. We employ nuanced computational text analytic tools that are new to this line of inquiry to assess the extent to which information in a brief is shared among all briefs and lower court opinions in the case. Using these measures, we investigate the relationship between novel and shared information and the content of Supreme Court opinions. We do so over the entire substantive content of a new dataset of more than 12, 000 litigant and amicus briefs filed in U.S. Supreme Court cases from 1988 to 2005. Our results provide new evidence that briefs presenting shared information are more likely to have that information adopted in the Court's majority opinion, raising interesting implications regarding majoritarianism.